Flow cytometry of hematological malignancies - Ortolani, C. (Claudio) (Hoboken, NJ : Wiley-Blackwell, 2021)
"Flow Cytometry of Hematological Malignancies contains an array of graphical outputs produced by the technique in the study of the most (and the least) common diseases. The images included allow you to compare your own results with a third party reference pattern. There is a detailed description of the main leukocyte antigens, together with a description of their distribution amongst normal and abnormal blood cells. The book also provides a comprehensive description of the phenotype of every neoplastic blood disease recorded in the WHO classification system, including all the instructions needed to recognise and classify even the least common entity. Designed to be practical, the book is perfect for quick consultation and is divided into two main sections. Section I deals with the direct object of immunophenotyping, and Section II deals with the ultimate target of the analysis. More than 50 antigens are covered and every antigen is dealt with in three main parts: general features, cytometric features and practical hints. This authoritative and state-of-the-art reference will be invaluable for clinicians directly involved in the diagnosis and analysis of hematological diseases, including hematologists, hematopathologists, oncologists, pathologists and technicians working in diagnostic laboratories"--
BIBINDX
Keywords: Hematological oncology; Flow cytometry; Hematologic Neoplasms -- diagnosis; Flow Cytometry -- methods; Electronic books